Clinical Factors Contributing to Age-Related Gait Dysfunction in Older Adults - Yoshihito Sakai MD, PhD; Tsuyoshi Watanabe MD, PhD; Norimitsu Wakao MD, PhD; Hiroki Matsui MD, PhD; Naoaki Osada MD; Yui Adachi MD; Yosuke Takeichi MD; Akira Katsumi MD, PhD; Ken Watanabe PhD (Geriatric Orthopaedic Surgery & Rehabilitation)
Objective As walking ability and balance deteriorate with age for bipedal humans, ambulating independently becomes cumbersome without using walking aids. However, age-related risk factors for loss of independent walking ability are not well characterized. We aimed to analyze the clinically relevant factors for ambulatory device aid from the perspectives of nutrition, body composition, and postural abnormalities between independent and assisted walkers based on their ambulatory status. Methods Among the 3640 patients aged ≥65 years initially enrolled in the study, 1557 patients with a history of fragility fractures were excluded. Patients were categorized into those who could walk independently and those who required assistance. Body composition, including skeletal muscle mass index, whole-spine sagittal alignment, and blood biochemical findings, were compared. Results Among the 2083 participants, 1323 and 760 were included in the independent and assisted groups, respectively. The logistic regression analysis identified five significant factors ( P < 0.01): age, body mass index, red blood cell distribution width, skeletal muscle mass index, and sagittal vertical axis. The receiver operating characteristic analysis determined the threshold for assisted walking to be age 81.0 years, red blood cell distribution width of 14.0%, skeletal muscle mass index of 5.96 kg/m 2 , and a sagittal vertical axis of 54.64 mm with areas under the curve of 0.727, 0.677, 0.645, and 0.708, respectively. Combining these four factors as propensity scores revealed an area under the curve of 0.768. Conclusion The comparison of independent and assisted walkers among older adults revealed the importance of age, red blood cell distribution width, skeletal muscle mass, and spinal sagittal balance as clinical factors of assisted walkers.